2015
DOI: 10.1016/j.vetimm.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific antinuclear antibodies in dogs using a line immunoassay and enzyme-linked immunosorbent assay

Abstract: Circulating antinuclear antibodies (ANA) are commonly present in the systemic autoimmune disease Systemic Lupus Erythematosus (SLE) and in other systemic rheumatic diseases, in humans as well as in dogs. The indirect immunofluorescence (IIF)-ANA test is the standard method for detecting ANA. Further testing for specific ANA with immunoblot techniques or ELISAs is routinely performed in humans to aid in the diagnosis and monitoring of disease. Several specific ANA identified in humans have been identified also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
0
16
2
Order By: Relevance
“…This is significantly lower than the concentration seen in the dogs with lymphoma reported in this study with median of 590 ng/mL. Comparisons between the concentrations of nucleosomes reported here and those in other reports of inflammation and control groups are difficult due to the fact that nucleosome concentrations have previously been reported only in arbitrary units(7)(8)(9)(20)(21)(22).…”
contrasting
confidence: 81%
“…This is significantly lower than the concentration seen in the dogs with lymphoma reported in this study with median of 590 ng/mL. Comparisons between the concentrations of nucleosomes reported here and those in other reports of inflammation and control groups are difficult due to the fact that nucleosome concentrations have previously been reported only in arbitrary units(7)(8)(9)(20)(21)(22).…”
contrasting
confidence: 81%
“…Several autoantigens have been previously identified in dogs by different approaches 9 , 21 , 22 , 38 , 46 50 . Here, we report the use of human protein arrays for the screening of canine autoantigens.…”
Section: Discussionmentioning
confidence: 99%
“…The standard test for detecting canine ANA – indirect immunofluorescence microscopy (IIF) – uses cells of human origin (HEp-2) as substrate 20 . In a previous study, it could be shown that several autoantibodies with important roles in human disease were also present in dogs 21 . Thus, the autoantibody targets in human and canine disease frequently overlap, although there are some autoantibodies that are species-specific 22 .…”
Section: Introductionmentioning
confidence: 95%
“…Previous work in dogs has reported AHA to be common in dogs suffering from SLE . Besides having a nuclear function, recent studies have indicated a significant toxic or pro‐inflammatory effect of histones when released into extracellular space by damaged and activated cells .…”
Section: Discussionmentioning
confidence: 99%
“…37 Previous work in dogs has reported AHA to be common in dogs suffering from SLE. 38 Besides having a nuclear function, recent studies have indicated a significant toxic or pro-inflammatory effect of histones when released into extracellular space by damaged and activated cells. 39 Histone release has been suggested to play a part in autoimmune disease, 40 not just acting as a direct autoantigen, but also magnifying the destructive autoimmune processes.…”
Section: Discussionmentioning
confidence: 99%